2016
DOI: 10.1152/ajpheart.00049.2016
|View full text |Cite
|
Sign up to set email alerts
|

Diastolic dysfunction in prediabetic male rats: Role of mitochondrial oxidative stress

Abstract: Although incidence and prevalence of prediabetes are increasing, little is known about its cardiac effects. Therefore, our aim was to investigate the effect of prediabetes on cardiac function and to characterize parameters and pathways associated with deteriorated cardiac performance. Long-Evans rats were fed with either control or high-fat chow for 21 wk and treated with a single low dose (20 mg/kg) of streptozotocin at week 4 High-fat and streptozotocin treatment induced prediabetes as characterized by sligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
75
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(89 citation statements)
references
References 88 publications
14
75
0
Order By: Relevance
“…Recently we showed that diet-induced obesity leads to decreased induction of autophagy in response to fasting in mice involving altered expression of numerous proteins related to metabolic pathways [15], which is in parallel to our current findings. However, in Long-Evans rats fed with high-fat diet we demonstrated only early signs of decreased mitophagy, but no major changes in overall cardiac autophagy or mTOR pathway [38]. In contrast, elsewhere metabolic syndrome induced by high-fat feeding increased cardiac LC3-II and SQSTM1/p62 in mice [39].…”
Section: Discussionmentioning
confidence: 99%
“…Recently we showed that diet-induced obesity leads to decreased induction of autophagy in response to fasting in mice involving altered expression of numerous proteins related to metabolic pathways [15], which is in parallel to our current findings. However, in Long-Evans rats fed with high-fat diet we demonstrated only early signs of decreased mitophagy, but no major changes in overall cardiac autophagy or mTOR pathway [38]. In contrast, elsewhere metabolic syndrome induced by high-fat feeding increased cardiac LC3-II and SQSTM1/p62 in mice [39].…”
Section: Discussionmentioning
confidence: 99%
“…Increased ROS production in the diabetic heart is a contributing factor in the development and progression of DCM. Koncsos et al reported that mild diastolic dysfunction and cardiac hypertrophy are associated with elevated oxidative stress in prediabetes, and prediabetes-induced oxidative stress originates from the subsarcolemmal mitochondria [15]. When ROS generation and ROS-degrading pathways are imbalanced, superoxide-mediated damage and cellular dysfunction will accumulate [16, 17].…”
Section: Discussionmentioning
confidence: 99%
“…Relative to the control, the contents of mitophagy-related proteins were significantly altered in several diabetic tissues including the heart. In male prediabetic rats, the generation of mitochondrial ROS increased and BNIP3 was downregulated in comparison with the corresponding values in the controls [14,114]. In types 1 and 2 diabetes models, PINK1 and Parkin were downregulated [109,115,116].…”
Section: Diabetic Cardiomyopathymentioning
confidence: 91%